Prosecutorial Evidence Efforts in Juvenile Violent Theft Cases: A Case Study at the Medan District Prosecutor’s Office - Sihombing, Ari Iswandy; Siregar, Hisar (Golden Ratio of Data in Summary, 2025)
This study discusses the efforts of the Public Prosecutor to provide evidence in a case of theft with violence committed by a minor at the Medan District Attorney's Office based on Decision Number 49/Pid.Sus-Anak/2025/PN.Mdn. The method used is normative juridical with a library approach through primary and secondary legal materials analyzed qualitatively. The results of the study indicate that the main causes of this crime include economic factors, low education, unemployment, victim negligence, bad company, and a consumptive lifestyle. The Public Prosecutor faced obstacles in the form of difficulty in presenting witnesses, low public legal awareness, and the child's uncooperative attitude. In providing evidence, statements from witnesses, the defendant, and valid evidence were submitted in accordance with Article 184 of the Criminal Procedure Code. The judge assessed that all elements of Article 365 paragraph (2) of the Criminal Code in conjunction with Law No. 11 of 2012 had been fulfilled, so the defendant was found guilty and sentenced to 1 year and 6 months. This research emphasizes the importance of the quality of evidence in order to achieve legal certainty, justice, and benefits, especially in cases of children who commit crimes.